THE CHALLENGES AND POSITIVE EFFECTS IN IMPLEMENTING STRATEGIES IN TEACHING TENSES - Sorohiti, Maryam; Ahna, Mila Farrihatul (Journal of Foreign Language Teaching and Learning, 2018)
AbstractIn addition to the benefits and problems of implementing strategies in teaching tenses, the implementation has brought challenges and effects to English teachers . This research aimed to explore the challenges faced by the teachers and the positive effects they enjoyed in implementing strategies in teaching tenses. This qualitative research was conducted at The Language Center of Universitas Muhammadiyah Yogyakarta. Interviews were administered to four female English teachers to explore their experiences in implementing strategies in teaching tenses. The finding revealed that technical problems, unsuccessful responses, managing time to prepare the strategies and selecting the appropriate materials were the challenges the teachers faced in implementing the strategies. Meanwhile, the increased students? motivation, improved students? attitude and understanding towards tenses, teachers? self-accomplishment as well as student?s awareness of the importance of tenses  were claimed as the positive effects from implementing the strategies in teaching tenses.            Keywords: tenses, teaching strategies, teaching challenges, positive effects